Reduced cerebrospinal fluid estradiol levels are associated with increased β-amyloid levels in female patients with Alzheimer's disease - Schönknecht, Peter; Pantel, Johannes; Klinga, Klaus; Jensen, Malene; Hartmann, Tobias; Salbach, Birgit; Schröder, Johannes (Neuroscience letters, 2001)
Recent in-vitro studies indicate that estrogens such as 17β-estradiol (E2) may decrease the production of β-amyloid 1-42 (Aβ42), a peptide central for the formation of senile plaques in Alzheimer's disease (AD). To test this hypothesis in a clinical study, cerebrospinal fluid levels of E2 were compared between 30 female AD patients and 11 female patients with non-dementing diseases such as major depression and investigated with respect to β-amyloid 1-40 and Aβ42 levels. E2 levels were significantly (P<0.05) lower in the AD group than in controls; within the AD group E2 levels were inversely correlated with Aβ42 concentrations (r=−0.36, P=0.05). This is the first clinical study providing evidence for an influence of E2 on Aβ42 metabolism in vivo. This observation corresponds to the putative beneficial effects of estrogen replacement therapy on the development and course of AD.